The commercial renting of wombs: surrogacy contracts / Nur Fathiah Najlaa Nasir ... [et al.] - Nasir, Nur Fathiah Najlaa; Hassan Hasri, Siti Khodijah; Said, Syuhadah; Zaini, Zati Hulwani (2011)
Surrogacy arrangements have become a popular solution to childless couples, especially in the West countries. Although it has not taken place in Malaysia, it is foreseeable that in some years ahead, surrogacy arrangements may become accepted by Malaysians. Therefore, this research proposes that Malaysia should have a specific law and regulations regarding surrogacy arrangements. In line with it, this research also analyses the laws on surrogacy arrangements in Malaysia and other countries. The analysis of the laws illustrates which law is the best and most suitable to be adopted in Malaysia. This research adopts the quantitative type of research techniques which is a library-based research and also the internet databases to gather information from the statutes, books, newspapers and articles relating to surrogacy. The purpose of this research is to analyze the existing laws on surrogacy in Malaysia and other countries, whilst proposing for certain legislative measures to be adopted in Malaysia. By this, the researchers hope that this research would point out on the importance of having a surrogacy law in Malaysia. Recommendations are also available where this research has provided the most possible criteria needed in regulating surrogacy law, which have also taken into consideration on Malaysian current existing law, its multiracial citizens, religions and other factors. However, the study in this research is limited to United Kingdom, Australia, Ukraine, India and Italy because these countries have various laws regarding surrogacy and it is easier to make comparison between them.